Dexamethasone alleviates etomidate-induced myoclonus by reversing the inhibition of excitatory amino acid transporters - Feng, Yan; Zhang, Min; Jia, Shuai-ying; Guo, Yan-xia; Jia, Xue (Frontiers in Neuroscience, 2024)
Background: Etomidate can induce myoclonus with an incidence of 50~85% during anaesthesia induction. Dexamethasone, as a long-acting synthetic glucocorticoid, has neuroprotective effects. However, the effects of dexamethasone on the etomidate-induced myoclonus remain uncertain.Methods: Adult male Sprague-Dawley rats were randomly assigned to receive etomidate (1.5 mg/kg) plus dexamethasone (4 mg/kg) (etomidate plus dexamethasone group) or etomidate (1.5 mg/kg) plus the same volume of normal saline (NS) (etomidate plus NS group). The mean behavioral scores, local field potentials and muscular tension were recorded to explore the effects of dexamethasone on etomidate-induced myoclonus. Liquid chromatography coupled with tandem mass spectrometric system (LC-MS/MS), quantitative real-time polymerase chain reaction (qRT-PCR), and western blotting were applied to analyze the levels of glutamate and γ-aminobutyric acid (GABA), the mRNA and protein expression of excitatory amino acid transporters (EAATs), and plama corticosterone levels at different time points after anaesthesia.Results: Compared with the etomidate plus NS treatment, the etomidate plus dexamethasone treatment significantly decreased the mean behavioral score at 1, 3, 4, and 5 min after administration; the peak power spectral density (PSD) (P=0.0197) in the analysis of ripple waves; and the glutamate level (P=0.0139) in the neocortex.However, compared with etomidate plus NS, etomidate plus dexamethasone increased the expression of the neocortical proteins of EAAT1 (P=0.0207) and EAAT2 (P=0.0022) and aggravated the inhibition of corticosterone at 4 h (P=0.0019), 5 h (P=0.0041), and 6 h (P=0.0009) after administration.Dexamethasone can attenuate the myoclonus, inhibit the glutamate accumulation, and reverse the suppression of EAATs in the neocortex induced by etomidate following myoclonus, while conversely aggravating etomidate-induced adrenal suppression.